Design of beamforming for IRS multi-partition-aided THz multi-subarray - Zufan ZHANG; Rui TANG (Tongxin xuebao)
In the IRS-aided THz communication system, in order to break the channel sparsity limitation on the system spatial multiplexing gain, a hybrid beam forming architecture with wide-spaced multi-subarrays at the transceiver/transmitter side was proposed and the transmission scheme of IRS multi-partition-aided THz multi-subarrays was designed.Firstly, a non-convex objective function with multivariate coupling and non-convex constraints was constructed based on the principle of maximizing spectrum efficiency.Then, the optimization problem was decoupled into two easy-to-solve sub-problems, namely, the reflection coefficient matrix design of IRS and the hybrid beamforming matrix design at the transceiver/receiver.Finally, the Riemannian manifold optimization algorithm was used to calculate the reflection coefficient matrix of IRS, and the closed solution of the hybrid beamforming matrix design at the transceiver/receiver was obtained through mathematical derivation.Simulation results show that compared with the baseline scheme, the proposed scheme can achieve better spectrum efficiency.